2017
DOI: 10.1002/fut.21853
|View full text |Cite
|
Sign up to set email alerts
|

The effects of investor attention on commodity futures markets

Abstract: This study utilizes the search volume for key terms on Google as a direct and timely proxy for investor attention in order to examine how attention impacts commodity futures prices, We provide significant evidence for attention's influence on 13 commodity futures and the interaction between attention and returns, even after controlling for important macroeconomic variables. We also examine the impact of investor attention on market efficiency. Results show that rising attention, on one hand, increases informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 53 publications
2
16
0
1
Order By: Relevance
“…Fourth, in order to focus on the possible distortions induced by the weeks with 0 searches ( which we replace by a very small arbitrary non-zero value 10 -11 in the main analysis to circumvent the logarithmic transformation issue), we provide three additional robustness checks for the long-short CFEAR portfolios constructed using the same methodology except for these changes: (i) as in Han et al (2017b) we replace the 0s by 1s so that the 0s are then turned into zero log search values, that is, (ii) the 0s in the search series are left as such and the Google search variable is instead defined as instead of , and (iii) although we consider weeks with zero searches informative, to dispel any remaining concerns, we remove the 0 data points from the calculations. These robustness checks are labelled (4a), (4b) and (4c), respectively.…”
Section: Alternative Approaches To Measure the Cfear Characteristicmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourth, in order to focus on the possible distortions induced by the weeks with 0 searches ( which we replace by a very small arbitrary non-zero value 10 -11 in the main analysis to circumvent the logarithmic transformation issue), we provide three additional robustness checks for the long-short CFEAR portfolios constructed using the same methodology except for these changes: (i) as in Han et al (2017b) we replace the 0s by 1s so that the 0s are then turned into zero log search values, that is, (ii) the 0s in the search series are left as such and the Google search variable is instead defined as instead of , and (iii) although we consider weeks with zero searches informative, to dispel any remaining concerns, we remove the 0 data points from the calculations. These robustness checks are labelled (4a), (4b) and (4c), respectively.…”
Section: Alternative Approaches To Measure the Cfear Characteristicmentioning
confidence: 99%
“…7 Through the lens of purely statistical criteria such as mean squared forecast errors, Han et al, (2017a) find that the Google search volume by oil-and real economy-related keywords are good predictors of oil futures returns relative to the historical average benchmark. Han et al (2017b) find that the predictive errors of commodity return models that include various macroeconomic variables decrease by adding as predictor the Google search volume by 13 commodity names and combinations thereof with various terms (e.g. cost, price, production and supply).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…The use of Google data has rapidly spread in the literature to predict other economic indicators such as unemployment (Choi and Varian, 2012;D'Amuri and Marcucci, 2017;Fondeur and Karamé, 2013;González-Fernández and González-Velasco, 2018), to analyze their impact on stock markets (Ben-Rephael, Da, and Israelsen, 2017;Gao, 2011, 2015), and to study bond markets (Dergiades, Milas, and Panagiotidis, 2015;Milas, Panagiotidis, and Dergiades, 2018) or their impact on commodities (Han, Li, and Yin, 2017;Peri, Vandone, and Baldi, 2014) with special attention to oil (Bampinas, Panagiotidis, and Rouska, 2019;Han, Lv, and Yin, 2017). However, related to the aim of this paper, some studies have shown conflicting results.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%